Clinical Decision Making: Integrating Advances in the Molecular Understanding of Spine Tumors. (15th October 2016) - Goodwin, C. Rory; Abu-Bonsrah, Nancy; Bilsky, Mark H.; Reynolds, Jeremy J.; Rhines, Laurence D.; Laufer, Ilya; Disch, Alexander C.; Bozsodi, Arpad; Patel, Shreyaskumar R.; Gokaslan, Ziya L.; Sciubba, Daniel M.; Bettegowda, Chetan
Abstract : Study Design: Literature review. Objective: To describe advancements in molecular techniques, biomarkers, technology, and targeted therapeutics and the potential these modalities hold to predict treatment paradigms, clinical outcomes, and/or survival in patients diagnosed with primary spinal column tumors. Summary of Background Data: Advances in molecular technologies and techniques have influenced the prevention, diagnosis, and overall management of patients diagnosed with cancer. Assessment of genomic, proteomic alterations, epigenetic, and posttranslational modifications as well as developments in diagnostic modalities and targeted therapeutics, although the best studied in nonspinal metastatic disease, have led to increased understanding of spine oncology that is expected to improve patient outcomes. In this manuscript, the technological advancements that are expected to change the landscape of spinal oncology are discussed with a focus on how these technologies will aid in clinical decision-making for patients diagnosed with primary spinal tumors. Methods: A review of the literature was performed focusing on studies that integrated next-generation sequencing, circulating tumor cells/circulating tumor DNA, advances in imaging modalities and/or radiotherapy in the diagnosis and treatment of cancer. Results: We discuss genetic and epigenetic drivers, aberrations in receptor tyrosine kinase signaling, and emerging therapeutic strategies that include receptor tyrosine kinase inhibitors, immunotherapy strategies, and vaccine-based cancer prevention strategies. Conclusion: The wide range of approaches currently in use and the emerging technologies yet to be fully realized will allow for better development of rationale therapeutics to improve patient outcomes. Level of Evidence: N/A